Resting pulmonary artery pressure of 21–24 mmHg predicts abnormal exercise haemodynamics. Issue 5 (10th March 2016) - Lau, Edmund M.T.; Godinas, Laurent; Sitbon, Olivier; Montani, David; Savale, Laurent; Jaïs, Xavier; Lador, Frederic; Gunther, Sven; Celermajer, David S.; Simonneau, Gérald; Humbert, Marc; Chemla, Denis; et al.
A resting mean pulmonary artery pressure (mPAP) of 21–24 mmHg is above the upper limit of normal but does not reach criteria for the diagnosis of pulmonary hypertension (PH). We sought to determine whether an mPAP of 21–24 mmHg is associated with an increased risk of developing an abnormal pulmonary vascular response during exercise. Consecutive patients (n=290) with resting mPAP <25 mmHg who underwent invasive exercise haemodynamics were analysed. Risk factors for pulmonary vascular disease or left heart disease were present in 63.4% and 43.8% of subjects. An abnormal pulmonary vascular response (or exercise PH) was defined by mPAP >30 mmHg and total pulmonary vascular resistance >3 WU at maximal exercise. Exercise PH occurred in 74 (86.0%) out of 86 versus 96 (47.1%) out of 204 in the mPAP of 21–24 mmHg and mPAP <21 mmHg groups, respectively (OR 6.9, 95% CI: 3.6–13.6; p<0.0001). Patients with mPAP of 21–24 mmHg had lower 6-min walk distance (p=0.002) and higher New York Heart Association functional class status (p=0.03). Decreasing levels of mPAP were associated with a lower prevalence of exercise PH, which occurred in 60.3%, 38.7% and 7.7% of patients with mPAP of 17–20, 13–16 and <13 mmHg, respectively. In an at-risk population, a resting mPAP between 21–24 mmHg is closely associated with exercise PH together with worse functional capacity. Resting mean PAP between 21–24 mmHg predicts abnormal exercise pulmonary haemodynamics and impaired functional capacity http://ow.ly/YfSuG